Impact of Silent Cerebral Embolism during and after Left Atrial Appendage Occlusion on Long‐Term Cognitive Function - Kexin Wang; Zhe Wang; Caiyi Jin; Mingjia Xu; Mingfang Li; Hailei Liu; Zidun Wang; Hongwu Chen; Weizhu Ju; Minglong Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Left atrial appendage occlusion (LAAO) was associated with a high incidence of procedure‐related silent cerebral embolism (SCE). There are limited data regarding the long‐term cognitive trajectory of patients undergoing LAAO. The aim of our study was to comprehensively assess the acute and long‐term impact of SCE during and after LAAO. Methods Consecutive patients with atrial fibrillation referred for LAAO from the First Affiliated Hospital with Nanjing Medical University between February 2021 and February 2023 were included. All patients underwent magnetic resonance imaging and cognitive assessments before and within 48 hours after the procedure. These evaluations were also repeated at 45‐day, 3‐month, 6‐month, and 1‐year follow up. Results Out of 75 patients included in the final analysis, 29 (38.7%) patients suffered from new SCE during LAAO. Patients with SCE exhibited a significant decline in cognitive function (Mini‐Mental State Examination) immediately after the procedure (P<0.001), which was not reversible during 1‐year follow‐up (P<0.001). Additionally, with time going on, the gap in cognitive function between patients with and without SCE became wider (SCE × 1 year: B=−4.81 [95% CI, −5.58 to −4.05]; P<0.001). New‐onset SCE was detected in 11 (14.7%) patients during the follow‐up magnetic resonance imaging, which also showed a decline in cognitive function (P=0.004). The results in Montreal Cognitive Assessment scores were consistent with Mini‐Mental State Examination. Conclusions LAAO‐related SCE is associated with a marked impairment in cognitive function immediately after the procedure and is irreversible over a 1‐year follow‐up. New magnetic resonance‐detected SCE during follow‐up after LAAO would also be associated with a decline in cognitive function.